Motor Identification in Students of SMP Negeri 32 Medan - Nico Febrian Gurning; Prama Uda Tarigan; Regtor Oliver; Octaviananda Siregar; Pras Dio Nanda (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This research aimed to identify and assess motor skills among students at SMP Negeri 32 Medan, focusing on both gross and fine motor abilities to establish baseline measurements for educational and developmental interventions. Methods: A cross-sectional observational study was conducted involving 30 elementary school students (ages 12-14 years) from SMP Negeri 32 Medan. Motor skill assessment included standardized tests for coordination, balance, agility, and fine motor control. Data were analyzed using descriptive statistics and correlation analysis. Results: The study revealed varying levels of motor skill development among participants, with significant correlations between age and motor performance. Gender differences were observed in specific motor domains, with males showing superior gross motor skills and females demonstrating better fine motor control. Conclusion: Motor skill identification provides valuable insights for developing targeted physical education programs and identifying students who may benefit from additional motor skill interventions